Penyediaan Poster Kreatif Tentang Pentingnya Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Sungai Turak - Yuly Safa’ati; Meldawati Meldawati; Siti Noor Hasanah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
One of the efforts to reduce MMR is by increasing the knowledge and skills of pregnant women, including regarding the danger signs of pregnancy. The class for pregnant women coordinated by the Sungai Turak village health center was felt to be less than optimal, where the level of attendance and motivation of mothers in attending the class for pregnant women was felt to be lacking. So a solution is needed to increase mothers' interest and motivation in attending classes for pregnant women held by the Sungai Turak Community Health Center. Completion by providing a creative poster about the importance of classes for pregnant women. The posters created are designed to be as attractive as possible, so that they get the attention of pregnant women who check their pregnancies at the Puskesmas/Posyandu. The poster design is made with minimal text, so that the poster can be more attractive. The posters also use regional languages to make them more interesting and familiar to read by local people. The poster also shows the schedule for holding classes for pregnant women at the Sungai Turak Community Health Center. Posters will be placed at community health centers, posyandu and village offices, as well as in shops frequently visited by the public.